Inhibition of arenavirus infection by thiuram and aromatic disulfides - Sepúlveda, Claudia Soledad (2010)
A selected group of aromatic disulfides, thiuram disulfides and thiosulfones, provided by the National Cancer Institute, were evaluated in vitro for their inhibitory activity against Junin virus (JUNV), the causative agent of Argentine hemorrhagic fever. The aromatic disulfides NSC4492 and NSC71033 and the thiuram disulfide NSC14560 were, respectively, the more potent virucidal and antiviral agents against JUNV, with inactivating concentration 50% (IC50) values of 0.2-0.5μM for virucidal compounds and antiviral effective concentration 50% (EC50) of 8.5μM for NSC14560. Both types of compounds exhibited inhibitory activity against three arenaviruses. Additionally, a comparable efficacy in the antiviral action of NSC14560 was observed in monkey, hamster or human cells with selectivity indices in the range 55.9-85.7. Time of addition experiments showed that the main antiviral activity of NSC14560 was situated before 5h of infection, but a significant inhibition was still observed when the compound was added up 9h p.i. This compound did not induce a refractory state to infection by cell pretreatment. Nor did it prevent viral entry, but the cytoplasmic and membrane expression of the main viral proteins was inhibited. The possible involvement of the RING finger motif of arenavirus Z protein as target for the thiuram disulfide is discussed.